A Quasi-Experimental Study on Lifestyle Education and Peripheral Circulation in Type 2 Diabetes Patients - Rahayu, Sri Mulyati; Suprapti, Tuti; Anri, Anri (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Type 2 diabetes mellitus (DM) poses a high risk for macrovascular complications such as Peripheral Arterial Disease (PAD). The Ankle Brachial Index (ABI) is a non-invasive, reliable screening tool for early detection of PAD. Lifestyle factors, particularly physical activity and dietary adherence, play a crucial role in maintaining vascular health. However, structured educational interventions integrating these aspects with ABI assessment remain limited. Objective: This study aimed to determine the effect of physical activity education and dietary compliance on ABI values in patients with type 2 diabetes mellitus. Methods: A quasi-experimental one-group pretest-posttest design was employed. Thirty type 2 DM patients from Riung Bandung Community Health Center and Bandung City Hospital participated in a 7-day structured educational intervention focusing on physical activity and diet. Data collection included a modified version of the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire and ABI measurements. Statistical analyses used Wilcoxon signed-rank test and Spearman correlation. Results: Post-intervention, participants showed improved dietary adherence (fruit/vegetable consumption increased from 3.2 to 4.9 days/week) and physical activity (specific exercise increased from 3.1 to 4.7 days/week). The mean ABI value increased from 0.94 to 1.02, with 80% of participants experiencing ABI improvement. There was a significant positive correlation between improved physical activity and dietary adherence with increased ABI values (p < 0.05). Conclusion: A 7-day structured educational intervention effectively improved physical activity and dietary compliance, leading to better vascular function as indicated by ABI improvement. This approach is promising for community-based prevention of vascular complications in type 2 DM patients